1998
DOI: 10.1161/01.cir.98.7.671
|View full text |Cite
|
Sign up to set email alerts
|

First Postpacing Interval Variability During Right Ventricular Stimulation

Abstract: FPPI variability may differentiate SMVT from AT and ST. This criterion is potentially useful in implantable devices that use a single ventricular lead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The variability was approximately twice lower in the case of slow (TCL≥350 ms) tachycardias. Ninety-five percent of the first and second assessments in the clinical measurements differed from one another by Limits of Agreement=19.6 ms. Arenal et al 24 assessed the variability of the first PPI during right ventricular pacing to differentiate between ventricular and supraventricular tachycardias in patients with implantable cardioverter-defibrillators. In their study, they analyzed 23 relatively slow VTs (mean TCL, 366±50 ms) and demonstrated that the difference between 2 PPI measurements was below 10 and 20 ms in 90% and 100% of the measurements, respectively, which is comparable to our results.…”
Section: Discussionmentioning
confidence: 99%
“…The variability was approximately twice lower in the case of slow (TCL≥350 ms) tachycardias. Ninety-five percent of the first and second assessments in the clinical measurements differed from one another by Limits of Agreement=19.6 ms. Arenal et al 24 assessed the variability of the first PPI during right ventricular pacing to differentiate between ventricular and supraventricular tachycardias in patients with implantable cardioverter-defibrillators. In their study, they analyzed 23 relatively slow VTs (mean TCL, 366±50 ms) and demonstrated that the difference between 2 PPI measurements was below 10 and 20 ms in 90% and 100% of the measurements, respectively, which is comparable to our results.…”
Section: Discussionmentioning
confidence: 99%